Solution Quality Improvements for Massively Multi-Agent Pathfinding - Wang, Ko-Hsin; Botea, Adi; Kilby, Philip (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
MAPP has been previously shown as a state-of-the-art multi-agent path planning algorithm on criteria including scalability and success ratio (i.e., percentage of solved units) on realistic game maps. MAPP further provides a formal characterization of problems it can solve, and low-polynomial upper bounds on the resources required. However, until now, MAPP’s solution quality had not been extensively analyzed. In this work we empirically analyze the quality of MAPP’s solutions, using multiple quality criteria such as the total travel distance, the makespan and the sum of actions (including move and wait actions). We also introduce enhancements that improve MAPP’s solution quality significantly. For example, the sum of actions is cut to half on average. The improved MAPP is competitive in terms of solution quality with FAR and WHCA*, two successful algorithms from the literature, and maintains its advantages on different performance criteria, such as scalability, success ratio, and ability to tell apriori if it will succeed in the instance at hand. As optimal algorithms have limited scalability, evaluating the quality of the solutions provided by suboptimal algorithms is another important topic. Using lower bounds of optimal values, we show that MAPP’s solutions have a reasonable quality. For example, MAPP’s total travel distance is on average 19% longer than a lower bound on the optimal value.